Evaluation the role of the nephrology team in the specific vascular access outpatient clinic. What can we contribute new? - Néstor Fontseré; Gaspar Mestres; Xavi Yugueros; Daniel Gil; Carla Blanco; Valentín Lozano; Lida María Rodas; Arantxa Gelabert; Paula Escarcena; Rosa Ramos; Francisco Maduell (Nefrología (English Edition))
Background and objectives: The key points of a monographic vascular access (VA) consultation are an adequate preoperative assessment, as well as a correct management and optimization of waiting lists. Our main objective of present study was to evaluate the degree of exploratory-dependent concordance in outpatient clinics regarding implanted VA, between nephrology and vascular surgery. Materials and methods: We analyzed VA created or surgically repaired between 2021 and 2022. We compared the differences in the preoperative variables between the groups in which the assessments between the two teams were coincident and non-coincident, and the primary (PP) and secondary (PS) patencies during the follow-up period (Kapplan-Meier curves and Log-rank test, and Cox regression analysis). Significant P ≤ 0.05. Results: A total of 605 VA creations or repairs were analyzed: 74 ligations (12.2%), 207 distal arterio-venous fistulaes (AVF) (34.3%), 237 proximal AVF (39.2%), 35 repairs (5.7%), 41 grafts (6.7%) and 11 others (1.9%). After an average waiting list time of 16.5 ± 11.6 days, excluding ligations, adequate 1-month maturation was observed in 87.6% of cases. A total of 158 endovascular procedures and 17 surgical repairs were performed during postoperative follow-up. Primary (PP) and secondary (PS) patencies at 6, 12 and 24 months were PP: 76.2%, 64.9%, 57.5% and PS: 86.4%, 81.2%, 74.7%, respectively. Of the total number of procedures, nephrology obtained an adequate degree of agreement in 93.6% of the cases (kappa index: 0.886). The preoperative factors associated with greater discrepancies in assessments were age (P = 0.022) and arterial diameter (P = 0.032). The subgroup of non-matched assessments between nephrology and vascular surgery (39 cases) presented a similar PP (at 2 years: 59.2% vs 41.3%, P = 0.099) but worse PS (at 2 years: 76.6% vs 55.4%, P = 0.005). Conclusions: No significant observer-dependent differences (nephrologist vs. vascular surgeon) were observed in decision-making regarding the surgical procedure to be performed (93.6% agreement), and discordant cases presented worse secondary patency. After specific training, the nephrology coordination team can make a proper optimisation of social and health resources by reserving referrals to vascular surgery for those cases of greater complexity. Resumen: Antecedentes y objetivo: Entre los puntos clave de una consulta monográfica de acceso vascular (AV) se encuentran una adecuada valoración preoperatoria, así como una correcta gestión y optimización de las listas de espera. El principal objetivo fue evaluar el grado de concordancia explorador-dependiente entre nefrología y cirugía vascular en una consulta externa monográfica respecto al AV finalmente implantado. Material y métodos: Se analizaron todos los AV creados o reparados quirúrgicamente entre los años 2021 y 2022. Se comparan las diferencias en las variables preoperatorias entre los grupos en los que las valoraciones entre ambos equipos fueron coincidentes y no coincidentes, la cirugía indicada y la permeabilidad primaria (PP) y secundaria (PS) durante el período de seguimiento (curvas de Kapplan-Meier y Log-rank test, y análisis de regresión de Cox). P significativa ≤ 0.05. Resultados: Se han analizado un total de 605 creaciones o reparaciones de AV: 74 ligaduras (12.2%), 207 FAVn distales (34.3%), 237 FAVn proximales (39.2%), 35 reparaciones (5.7%), 41 FAVp (6.7%) y 11 otros procedimientos (1.9%). Tras un tiempo medio en lista de espera de 16.5 ± 11.6 días, excluyendo las ligaduras, se observó una adecuada maduración al mes en el 87.6% de los casos. En el seguimiento postoperatorio se realizaron un total de 158 procedimientos endovasculares y 17 reparaciones quirúrgicas. Las permeabilidades primarias (PP) y secundaria (PS) a 6, 12 y 24 meses, fueron PP: 76.2%, 64.9%, 57.5% y PS: 86.4%, 81.2%, 74.7%, respectivamente. De total de los procedimientos nefrología obtuvo respecto a cirugía vascular un adecuado grado de concordancia en el 93.6 % de los casos (índice Kappa: 0.886). Los factores preoperatorios significativos entre los casos coincidentes y no coincidentes fueron la edad (P = 0.022) y el diámetro arterial (P = 0.032). El subgrupo de valoraciones no coincidentes entre nefrología y cirugía vascular (39 casos), presentaron una similar PP (a 2 años: 59,2% vs 41.3%, P = 0.099) pero peor PS (a 2 años: 76.6% vs 55.4%, P = 0.005). Conclusiones: No se observaron diferencias significativas observador dependiente (nefrólogo vs. cirujano vascular) en la toma de decisiones en cuanto al acto quirúrgico a realizar (93.6% de coincidencia), y los casos discordantes presentaron peor permeabilidad secundaria. Tras una formación específica, el equipo de coordinación de nefrología puede realizar una adecuada optimización de los recursos socio sanitarios reservando las derivaciones a cirugía vascular para aquellos casos de mayor complejidad.